Computers tools in construction - Idrus, Arazi; Utomo, Christiono; Hisyam, Ikmal (2008)
Applications of computer tools are very important in the construction site. However, what is the actual level of usage of computer tools in construction field in Malaysia? Do they aware of the availability of this tool in the market? Do they know the advantages for using this computer tools in construction industry? A survey need to be done to identify the current states of computer tools application in Malaysia’s construction industry. It will be conducted to provide information on the awareness and perception of computer tools among construction professionals.